Influence Of Indium Substitution And Microstructure Changes On The Magnetic Properties Evolution Of Y3fe52xinxo12 (x =0.0–0.4) - Rodziah Nazlan; Mansor Hashim; Idza Riati Ibrahim; Fadzidah Binti Mohd Idris; Wan Norailiana Wan Ab Rahman; Nor Hapishah Abdullah; Ismayadi Ismail; Samikannu Kanagesan; Zulkifly Abbas; Raba'ah Syahidah Azis (Springer Science and Business Media LLC, 2024)
Indexed by Scopus